Intelligent Agent Facilitated e-Commerce - Sabyasachi Pramanik, Ramkrishna Ghosh (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The depiction and execution of a multidisciplinary fact-finding design including a smart agent-based architecture for collective e-commerce operations are presented in this article. A Multi-Agent System (MAS) structure is designed and developed for multidiscipline ecommerce settings including a variety of globally distributed consumers and merchants. This framework is distinct from other current e-Commerce systems in that it not merely uses agent technologies in new ways in e-commerce systems, but it also integrates the law on privacy and regulation into its technological framework.